Om pragmatiska fraser i Svensk konstruktionsordbok - Clausén, Ulla (Nordiske Studier i Leksikografi, 1997)
The purpose ofthis paper is to discuss the way pragmatic phrases, e.g. phrases of the type affärer är affärer ’business is business’, det är inte att ta till överord ’this is no overstatement’, när allt kommer omkring ’after all’ and snälla nån ’Good gracious’ are treated in the forthcoming phraseological dictionary "Svensk konstruktionsordbok". Typical of phrases of this type is their pragrnatic function, i.e. the function to express views, feelings and attitudes in a standardized way. Among the pragmatic phrases I distinguish one main group, cliches, which contains platitudes, discourse organizers and formulaic speech. The formulaic speech contains phrases of conversation, polite phrases, threats, warnings and prohibitions. In order to use these phrases correctly the user of a phraseological dictionary needs more than just a statement of the meaning ofthe phrases. Information should be given both about functional use and attitudes. A mode! for analysis ofpragmatic phrases is introduced.